Human-animal entanglements: urban ecologies of care, compassion, pity and disgust for Baladi dogs in Cairo (Egypt) - Bradshaw, Kezra Rose (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.